2022
DOI: 10.1038/s41467-022-34530-z
|View full text |Cite
|
Sign up to set email alerts
|

Site-selective photocatalytic functionalization of peptides and proteins at selenocysteine

Abstract: The importance of modified peptides and proteins for applications in drug discovery, and for illuminating biological processes at the molecular level, is fueling a demand for efficient methods that facilitate the precise modification of these biomolecules. Herein, we describe the development of a photocatalytic method for the rapid and efficient dimerization and site-specific functionalization of peptide and protein diselenides. This methodology, dubbed the photocatalytic diselenide contraction, involves irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 98 publications
2
11
0
Order By: Relevance
“…Moreover, the formation of a selenolanthionine bridge from cyclic peptides involving both intramolecular diselenide and disulfide bonds was achieved in 10 min of irradiation without affecting the disulfide bond [ 90 ]. A similar reaction was later described by Dowman et al [ 131 ], who demonstrated the photocatalytic diselenide contraction to yield selenoethers. This transformation was induced by irradiation of Sec-containing dimers in the presence of the phosphine 1,3,5-triaza-7-phosphaadamantane (PTA) and the iridium photocatalyst, [Ir(dF(CF 3 )ppy) 2 (dtbpy)]PF 6 , under LED 450 irradiation within 5 min.…”
Section: Photochemical Reactions Of Selenium-containing Peptidessupporting
confidence: 54%
“…Moreover, the formation of a selenolanthionine bridge from cyclic peptides involving both intramolecular diselenide and disulfide bonds was achieved in 10 min of irradiation without affecting the disulfide bond [ 90 ]. A similar reaction was later described by Dowman et al [ 131 ], who demonstrated the photocatalytic diselenide contraction to yield selenoethers. This transformation was induced by irradiation of Sec-containing dimers in the presence of the phosphine 1,3,5-triaza-7-phosphaadamantane (PTA) and the iridium photocatalyst, [Ir(dF(CF 3 )ppy) 2 (dtbpy)]PF 6 , under LED 450 irradiation within 5 min.…”
Section: Photochemical Reactions Of Selenium-containing Peptidessupporting
confidence: 54%
“…A large anodic oxidation signal was observed at 1.05 V, corresponding to the oxidation of TPPTS to the radical cation (as seen in Figure 2A). We postulated that following oxidation, the electrochemical modification strategy would proceed through an analogous single‐electron mechanism to that proposed for photocatalytic contraction reactions at Sec [7a] . Briefly, we hypothesized that the radical cation generated from anodic oxidation of the phosphine would induce homolytic diselenide cleavage, with cathodic reduction of the resultant selanyl radical generating one equivalent of a highly nucleophilic selenolate (Figure 2B).…”
Section: Resultsmentioning
confidence: 96%
“…The development of this proposed electrochemical modification chemistry took inspiration from a photocatalytic diselenide contraction (PDC) transformation recently developed in our laboratory (Figure 1A). [7a] The PDC method employs an iridium photocatalyst ([Ir(dF(CF 3 )ppy) 2 (dtbpy)]PF 6 ) together with a phosphine and irradiation at 450 nm to convert asymmetric or symmetric diselenide starting materials to their corresponding selenoether‐linked products, with formal extrusion of a selenium atom. We sought to overcome key limitations of this methodology, including incompatibility with fluorogenic substrates and the use of expensive and poorly aqueous soluble photocatalysts, through the development of a low cost, atom economic, and biocompatible electrochemical method for site‐selective functionalization of Sec residues, coined electrochemical selenoetherification (e‐SE).…”
Section: Introductionmentioning
confidence: 99%
“…They also reported conversion of dimeric peptide diselenides to dimeric peptide selenoethers with phosphine, an iridium photocatalyst, and light, which can be applied to late-stage modification of synthetic peptides. 71 Andrey A. Ivanov (Emory University, USA) shared protein−protein interactions (PPIs) in breast cancer discovered with their quantitative high-throughput differential screening (qHT-dS), which was first shared at ICBS 2017 and used in wildtype and mutant systems of lung cancer and other cancers. 72 The qHT-dS platform discovered mitogen-activated kinase kinase 3 (MKK3), previously only known to activate tumor suppressor p38 by phosphorylation, to activate the transcription factor MYC by PPI.…”
Section: ■ Daymentioning
confidence: 99%
“…The technique was used to generate other proteins and adapted for protein generation in one pot. They also reported conversion of dimeric peptide diselenides to dimeric peptide selenoethers with phosphine, an iridium photocatalyst, and light, which can be applied to late-stage modification of synthetic peptides …”
Section: Daymentioning
confidence: 99%